High-Metastatic Melanoma Cells Promote the Metastatic Capability of Low-Metastatic Melanoma Cells via Exosomal Transfer of miR-411-5p - Chen, Hao; Zeng, Bin; Li, Xiaoshuang; Zhao, Qiting; Liu, Doudou; Chen, Yuting; Zhang, Yuhan; Wang, Jianyu; Xing, H. Rosie (Frontiers in Oncology, 2022)
Melanoma is characterized by high rate of metastasis and mortality. Effective management of metastatic melanoma depends on renewed mechanistic understanding underlying melanoma progression and metastasis. The role of exosomes in mediating the interactions between cancer cells and the metastatic microenvironment is at the forefront of cancer research. Previous researches on the function of exosomes in metastasis have been primarily focused on tumor cell-derived exosomes in modifying the biological functions of stromal cells. Whether the cancer cells at the involved organ can modify the metastatic capability of each other has not been demonstrated. In this study, a paired M14 melanoma derivative cell line, i.e., M14-OL and POL, that we established and characterized were employed. Oligo-metastatic (M14-OL) and poly-metastatic (M14-POL) cell line were generated from three consecutive rounds of in vivo selection and passage. They exhibit high (POL cells) and low (OL cells) metastatic colonization efficiency in vivo, respectively. We show that exosomal crosstalk between metastatic cancer cells is a new mechanism of cancer metastasis. High-metastatic melanoma cells (POL) can augment the metastatic colonization capability of the low-metastatic melanoma cells (OL). POL achieves this goal by utilizing its exosomes to deliver functional miRNAs, in this case, miR-411-5p, to the OL cell. Upon entering OL cells, exosomal miR-411-5p enhance metastatic colonization efficiency by activation of the ERK signaling pathway. Moreover, miR-411-5p expression is higher in cancer tissues of other cancer types (colon, lung, rectum) compared with that of respective normal tissues. The clinical relevance of the present finding merits future investigations.